The Construction of Affordable Housing in Developing Countries: a Scientometric Review - Deddy Purnomo Retno; Harmiyati Harmiyati (Journal of Applied Engineering and Technological Science (JAETS), 2023)
The presence of affordable housing in developing countries is a crucial issue in order to fulfill the primary need for housing in a large market segment, especially people whose income is below the average household income. In contrast to developed countries, the development of studies on affordable housing construction (AHC) in developing countries has not been well mapped. This certainly creates many gaps in determining the direction of future developments, especially related to the studies that will be carried out. This study tries to map the development of scientific publications related to AHC  in developing countries, from 1983 - 2021. Using scientometric techniques and VosViewers as a data processing tool, 116 publications that meet the given criteria have been identified. The findings of this study reveal a mapping of publications organized by country, organization, research outlet, author, document citation, and main research area. During the observation period, most research focused on developing nations, affordability, sustainable development, the construction industry, and the developing globe. In addition, the results of this study also successfully mapped opportunities for future research focuses related to building materials, affordable housing, low-income populations, decision-making, and structural design. In conclusion, this study highlights the need for further research on affordable housing development in developing countries to guide policy makers and researchers in developing affordable housing solutions that meet the housing needs of low-income households.